1987
DOI: 10.1097/00006842-198701000-00004
|View full text |Cite
|
Sign up to set email alerts
|

A follow-up study of thirty hospitalized bulimics.

Abstract: Thirty normal-weight female bulimics were followed up 2-5 years following hospital admission using semistructured interviews and psychometric measures. Inasmuch as bulimia was only recently designated a distinct disorder, questions have emerged with regard to its clinical course and diagnostic validity. Results of this investigation suggest that bulimia displays a chronic but tractable course in that the majority of the patients continued to report bulimic behaviors at follow-up but the symptom intensity was g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0
1

Year Published

1988
1988
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 30 publications
5
37
0
1
Order By: Relevance
“…These patients often have a better prognosis than those who function poorly and whose disordered eating symptoms are of sufficient severity to merit hospitalization. 31 As expected, the control group, which was not treated in our program, had statistically significant lower scores regarding symptom withdrawal, as well as for sexuality and social adjustment scores. However, although most patients in this group did not receive multimodal treatment, many had spontaneous improvement in the measured variables.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…These patients often have a better prognosis than those who function poorly and whose disordered eating symptoms are of sufficient severity to merit hospitalization. 31 As expected, the control group, which was not treated in our program, had statistically significant lower scores regarding symptom withdrawal, as well as for sexuality and social adjustment scores. However, although most patients in this group did not receive multimodal treatment, many had spontaneous improvement in the measured variables.…”
Section: Discussionsupporting
confidence: 73%
“…28 Relapse rates between 30% and 50% have been reported for successfully treated patients after 6 months to 6 years of follow-up, and some data suggest that slow improvement continues as the period of follow-up extends to 10 to 15 years. [27][28][29][30][31] In a large study of the longterm course of patients with bulimia nervosa, 6 years after successful treatment in an intensive program, 30 outcomes of 60% of the patients were rated as good, 29% were of intermediate success, and 10% were poor, with 1% deceased. Kordy et al 25 also reported a 60% improvement in symptoms among bulimic patients at a 2.5-year follow-up, but only 18% achieved full remission and 16% were considered recovered.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, Swift and colleagues (72), reporting on a small sample of women with BN at least two years after discharge from hospital, found that 27% were asymptomatic, 40% had an intermediate outcome, and the remaining 33% had a poor outcome with "bingeing or purging on a daily basis." Weight fluctuations and dissatisfaction with their body persisted.…”
Section: Studies Of the Outcome Of Bn And Anmentioning
confidence: 99%
“…It is possible that the numerous studies that did not include information regarding crossover found no crossover to anorexia nervosa, as was specifically reported for two cohorts (3,14,20,21,44). From the research reviewed, it appears that the rate of crossover from bulimia nervosa to anorexia nervosa is much smaller than the crossover from anorexia nervosa to bulimia nervosa at follow-up (estimated range=10% to 50%) (46).…”
Section: Crossovermentioning
confidence: 96%